Observation of a flavin semiquinone in the resting state of monoamine oxidase B by electron paramagnetic resonance and electron nuclear double resonance spectroscopy - (:unkn) unknown (My University, 1996)
Monoamine oxidase (MAO) plays an essential role in the regulation of various neurotransmitter and xenobiotic amines. Inhibitors of MAO have been employed in the treatment of depression and as adjuncts in Parkinson's disease therapy. X-Band and Q-band electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) spectroscopic techniques are employed to characterize a signal assigned as a stable red anionic semiquinone radical in the resting state of MAO B. It is shown thai the radical signal is not affected during substrate (either benzylamine or phenylethylamine) turnover, by anaerobic incubation with substrate, or by covalent modification of the active site flavin cofactor in the catalytically active dimer. Upon denaturation, however, the semiquinone absorbances and EPR signals are lost. Photoreduction of the native enzyme in the presence of ethylenediaminetetraacetate generates an EPR signal that is not the same as that obtained in the resting state and shows different proton ENDOR signals. These results suggest that the two flavin prosthetic groups that exist in catalytically active monoamine oxidase B are physically distinct.